Properties of fractional Brownian motions for modeling stock prices - Mamat, M.; Prabowo, A.; Sugandha, A.; Tripena, A.; Dewi, W.S.; Sukono, .; Bon, A.T.
Fractional Brownian motion is a general form of Brownian motion by adding a parameter / index, namely the Hurts index. Modeling stock prices with Brownian motion is common. In this article we will discuss fractional Brown motion for modeling stock prices . Some of these properties are increments which are normally distributed and not mutually independent, self-similarity and longrange dependent.